Transient Bilateral Common Carotid Artery Occlusion (tBCCAO) of Rats as a Model of Global Cerebral Ischemia - Handayani, Ety Sari; Susilowati, Rina; Setyopranoto, Ismail; Partadiredja, Ginus (Bangladesh Journal of Medical Science, 2019)
Background: Transient bilateral common carotid artery occlusion (tBCCAO) has been performed in rats as a model of global ischemia. However, the technique varied between laboratories and produced difficulties in the comparison of results. Variations such as rat strain, age, ischemic and reperfusion duration could affect the results. This review aims to provide a general overview of the variation of animal strains, duration of tBCCAO, reported cerebral ischemic area produced by tBCCAO, use of TTC staining for measurement of volume of brain ischemia and functional neurological tests. Method: The data of this review were obtained from abstracts in PubMed database and Google Scholars and were not limited by publication time. Keywords used to search the abstracts were (BCCAO OR “bilateral common carotid artery occlusion” OR “stroke” OR “cerebral ischemia” OR “brain ischemia”) AND (rat OR rats). The research method of each study was identified from the collected abstracts. The abstracts were chosen for further study on the basis that they met the inclusion criteria which were English language articles; original research article; animal model used were adolescent, adult, and elderly rats; ischemic finding in rats’ cerebrum by BCCAO technique was presented; ischemic size were assessed and the result was described; studies that had control group; and studies that induced transient global ischemic to the rats’ cerebrum. Data that were extracted to the datasheet were references; animal model strain; ischemic duration; reperfusion duration; ischemic area; 2,3,5 Triphenyltetrazolium Chloride (TTC) staining; Cavalieri method; and rats’ neurological functional tests. Results and Conclusions: There were differences in the ischemic area between Wistar and Sprague-Dawley rats after transient BCCAO. There were differences in the TTC staining solution concentration that was used to identify ischemic area of the brain following transient BCCAO. There was a very limited number of studies using Cavalieri method for the quantification of ischemic volume of rats’ brain after transient BCCAO. Neurological functional tests in animal models post transient BCCAO did not include sensory and memory functions tests. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.491-500